The Indonesian Version of the Skills, Confidence, and Preparedness Index (SCPI) was tested for reliability and validity in type 2 diabetes patients - Kurnia, Anih; Said, Farida Mohd; Paduragan, Santhna Letchmi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Although several diabetes self-care management tools have been created, very few provide preparation for diabetes self-care behavior management. Three essential components of diabetes self-care management are measured by the assessment tool